Elastic–plastic intermittent re-arrangements of frictionless, soft granular matter under very slow isotropic deformations - Luding, Stefan (Frontiers in Physics, 2023)
How do soft granular materials (or dense amorphous systems) respond to externally applied deformations at different rates and for different system size? This long-standing question was intensively studied for shear, but only more recently also for isotropic deformations, like compression-decompression cycles. For moderate strain rates, in the solid-like state, above jamming, the system appears to evolve more or less smoothly in time/strain, whereas for slow enough deformations, the material flips intermittently between the elastic, reversible base-state and plastic, dynamic "events". Only during the latter events the micro-structure re-arranges, irreversibly. The reversible base state involves both affine and non-affine deformations, while the events are purely non-affine. The system size and rate dependence of the events is studied, providing reference data, to be compared in future to experiments on materials like hydrogel particles using modern techniques.